NCOA4-Mediated Ferritinophagy: A Potential Link to Neurodegeneration - Quiles del Rey, Maria; Mancias, Joseph D. (Frontiers in Neuroscience, 2019)
NCOA4 (Nuclear receptor coactivator 4) mediates the selective autophagic degradation of ferritin, the cellular cytosolic iron storage complex, thereby playing a critical role in intracellular and systemic iron homeostasis. Disruptions in iron homeostasis and autophagy are observed in several neurodegenerative disorders raising the possibility that NCOA4-mediated ferritinophagy links these two observations and may underlie, in part, the pathophysiology of neurodegeneration. Here, we review the available evidence detailing the molecular mechanisms of NCOA4-mediated ferritinophagy and recent studies examining its role in systemic iron homeostasis and erythropoiesis. We propose additional studies to examine the potential role of NCOA4 in the brain in the context of neurodegenerative diseases.